2017
DOI: 10.1080/10803548.2017.1314120
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of electromyography normalization of the neck and shoulder muscles in symptomatic office workers

Abstract: Peak rms and MF from the MVIC normalization method can be measured with sufficient repeatability in symptomatic office workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Our reliability study of sEMG measurements during the three tasks confirmed that the sEMG is a reliable tool for the measurement of neck and shoulder muscle activity in dentists. These findings coincide with authors such as Chaikumarn et al [34], whose study population was office workers with cervical symptoms, and Machado et al [35], who performed measurements on women with and without neck-shoulder symptoms. We were unable to find reliability studies of the sEMG on dentists.…”
Section: Discussionsupporting
confidence: 90%
“…Our reliability study of sEMG measurements during the three tasks confirmed that the sEMG is a reliable tool for the measurement of neck and shoulder muscle activity in dentists. These findings coincide with authors such as Chaikumarn et al [34], whose study population was office workers with cervical symptoms, and Machado et al [35], who performed measurements on women with and without neck-shoulder symptoms. We were unable to find reliability studies of the sEMG on dentists.…”
Section: Discussionsupporting
confidence: 90%
“…An electromyographic activity is a neuromuscular response to biomechanical activity. The most widely used method to get the reference value of muscle activation for normalizing EMG signals has been the use of maximum voluntary isometric contraction [21][22][23]. During isometric contractions, a welldefined relationship exists between the magnitude of voluntary muscle activity and the EMG signal amplitude [24].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, to estimate a maximum voluntary contraction (MVC) for the upper trapezius, subjects placed their hand at 90 0 abduction, sitting down on a chair, and were asked to apply pressure against the exposed resistance at the top [25].…”
Section: Electromyographymentioning
confidence: 99%
“…Then, the head was anterolaterally placed and pressurised against the hand resistance [21]. To obtain the MVC for the erector spinae muscle, the subjects were asked to be in a prone posture and put both hands behind their head as moving the overhand against the resistance in the extension direction [25]. To achieve MVC for the diaphragm muscle in the sitting position subjects took deep breaths [26].…”
Section: Electromyographymentioning
confidence: 99%
See 1 more Smart Citation